Essential dads : the inequalities and politics of fathering - Randles, Jennifer M. (University of California Press, 2020)
"In Essential Dads, sociologist Jennifer Randles shares the stories of more than 60 marginalized men as they sought to become more engaged parents through a government-supported "responsible" fatherhood program. Dads' experiences serve as a unique window into long-standing controversies about the importance of fathering, its connection to inequality, and the state's role in shaping men's parenting. With a compassionate and hopeful voice, Randles proposes a more equitable political agenda for fatherhood, one that carefully considers the social and economic factors shaping men's abilities to be involved in their children's lives and the ideologies that rationalize the necessity of that involvement"-- Provided by publisher.
Keywords: Fatherhood -- United States -- Case studies.; Fatherhood responsibility movement -- United States -- Case studies.; Parenting -- United States -- Case studies.; Equality.; Paternité -- États-Unis -- Études de cas.; Rôle parental -- États-Unis -- Études de cas.; Paternité responsable -- États-Unis -- Études de cas.; SOCIAL SCIENCE / Gender Studies; Equality; Fatherhood; Fatherhood responsibility movement; Parenting; United States; Case studies